Impact of dry eye on reading in a population-based sample of the elderly: the Salisbury Eye Evaluation. Issue 5 (11th October 2013) - van Landingham, Suzanne W; West, Sheila K; Akpek, Esen K; Muñoz, Beatriz; Ramulu, Pradeep Y
Abstract : Background/aims: People with dry eye often complain of difficulty reading, but this perceived deficit has not been appropriately quantified. The purpose of this study is to determine if dry eye is associated with measurable reading deficits. Methods: A cross-sectional study of 1981 participants in the Salisbury Eye Evaluation, a population-based study of the elderly. Dry eye symptoms were identified by questionnaire and clinically significant dry eye was defined as the presence of dry eye symptoms and positive Schirmer testing or ocular surface staining in either eye. Spoken reading speed was measured using short text passages. Subjects self-reported if they did not read or had difficulty reading newsprint. Results: 13.8% of subjects (274/1981) had dry eye symptoms and 3.1% (62/1981) had clinically significant dry eye. There was no difference in reading speed between subjects with dry eye symptoms or clinically significant dry eye and their controls (p=0.99 and 0.78, respectively) in multivariable models. Compared with asymptomatic subjects, however, subjects with dry eye symptoms were more likely to report reading difficulty (OR=1.7, 95% CI 1.3 to 2.4, p<0.01) and not reading newsprint (OR=1.9, 95% CI 1.0 to 3.6, p=0.04). Similarly, subjects with clinically significant dry eye were more likely to report difficulty reading newsprint (OR=2.5, 95% CI 1.4 to 4.5, p<0.01) or not reading newsprint at all (OR=4.1, 95% CI 1.6 to 10.7, p<0.01) as compared with subjects without dry eye signs or symptoms. Conclusions: Dry eye did not significantly affect reading speed but was associated with self-reported reading difficulty and avoidance of newspaper reading in this elderly population-based sample.